CURRENT STATE OF DEVELOPMENT OF UZBEK AUDITING STANDARDS IN ACCORDANCE WITH INTERNATIONAL AUDITING (Conferencea, 2023)
Along with international standards, each country has national auditing standards. They may be determined by law, regulations or an authorized body of a given country. Their use is mandatory when conducting an audit of financial statements or providing audit-related services. In addition to mandatory standards, the authorized body or professional audit organizations of the country can develop and adopt at the local level provisions on national audit practices recommended for use by auditors when conducting an audit.